Comparative analysis of the wear of titanium/titanium and titanium/zirconia interfaces in implant/abutment assemblies after thermocycling and mechanical loading - Almeida, Paulo J. (2016)
Objectives: Due to its hardness, zirconia abutments may damage the titanium of the implant's connection during its clinical use. This study aimed to assess the wear of the seating platforms of externally hexed titanium implants when connected to zirconia abutments comparing to titanium abutments, after thermocycling and mechanical loading (TCML).Methods: Six BNT (R) S4 external connection implants (Phibo (R) Dental Solutions, Barcelona, Spain) were selected and divided into two groups (n=3): TiCE, screwed to titanium abutments and ZrCE, screwed to zirconia abutments. The samples underwent thermocycling (5000 cycles; 5-55 degrees C) and mechanical loading (1.2 x 106 cycles; 88.8 N; 4 Hz). Before and after TCML, the seating platforms of the implants were analyzed by 3D profilometry in two areas to measure their topography based on the superficial analysis parameters (Sa and Sz) parameters, and were studied by scanning electron microscopy (SEM). Data were statistically analyzed by Mann-Whitney test (p <0.05).Results: No statistically significant differences were observed in the Sa and Sz values between the implants at initial state and after TCML (p = 0.573> 0.05 and p = 0.059). The abutment's material (titanium/zirconia) did not statistically significantly influence the Sa and Sz values after TCML (p = 0.886> 0.05 and p = 0.200, respectively). However, the SEM analysis reveals a mild wear in some vertices of the hex when connected to zirconia abutments.Conclusions: After simulating five years of clinical use, the externally hexed implants, analyzed by 3D profilometry, showed similar wear patterns in the corresponding seating platforms when connected to zirconia or titanium abutments. The SEM images showed zirconia particles being transferred to the implant, which requires further study. (C) 2016 Sociedade Portuguesa de Estomatologia e Medicina Dentaria.